On the Consequences of Meaning Selection: Perspectives on Resolving Lexical Ambiguity.
DOI: 10.1037/10459-010
|View full text |Cite
|
Sign up to set email alerts
|

The role of inhibition in meaning selection: Insights from retrieval-induced forgetting.

Abstract: lAs will become clear in later sections, we have questioned the assumption that stronger competitors cause more forgetting. Our work indicates that stronger competitors do not impair recall probability of targets, given that (a) the time given for recall is not overly constrained and (b) the contribution of output inhibition from stronger competitors is controlled (M. C. Anderson et al., 1994; Anderson, Bjork, & Bjork, 2000). We agree that stronger competitors increase retrieval time for a target, making that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
95
1

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(110 citation statements)
references
References 0 publications
14
95
1
Order By: Relevance
“…Thus, inhibition appears to be most heavily recruited during the early stages of second-language acquisition, thereby facilitating retrieval of the weaker, foreign language in the face of the otherwise overwhelming dominance of the native vocabulary. This finding is consistent with interference dependence, the finding that retrieval only inhibits related traces to the extent that they pose a considerable threat of interference (Anderson et al, 1994;Shivde & Anderson, 2001).…”
Section: Inhibition In Selective Retrievalsupporting
confidence: 79%
See 2 more Smart Citations
“…Thus, inhibition appears to be most heavily recruited during the early stages of second-language acquisition, thereby facilitating retrieval of the weaker, foreign language in the face of the otherwise overwhelming dominance of the native vocabulary. This finding is consistent with interference dependence, the finding that retrieval only inhibits related traces to the extent that they pose a considerable threat of interference (Anderson et al, 1994;Shivde & Anderson, 2001).…”
Section: Inhibition In Selective Retrievalsupporting
confidence: 79%
“…If forgetting is produced solely by strengthening practiced items, then doing so through extra exposure without actual retrieval practice should be just as effective in reducing the final recall of unpracticed competitors. Contrary to a noninhibitory account, such conditions fail to produce RIF, despite facilitating the practiced items to the same degree as does retrieval practice (Anderson & Bell, 2001;Anderson, Bjork, & Bjork, 2000;Bä uml, 1996Bä uml, , 1997Bä uml, , 2002Ciranni & Shimamura, 1999;Shivde & Anderson, 2001). Thus, RIF appears to be specifically induced by retrieval and dissociable from the degree to which practiced items are strengthened.…”
Section: Inhibition In Selective Retrievalmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, previous studies have shown that retrieval of (Anderson et al, 1994) and cuing with 3 learned category exemplars impairs recall of a category's high-frequency, but not a category's lowfrequency, exemplars. This result is important, since the high-low difference is consistent with retrieval inhibition but is inconsistent with retrieval competition (Anderson et al, 1994, Appendix A; see also Shivde & Anderson, 2001). Together, these findings support the proposal that the detrimental effect of part-list cuing is caused by retrieval inhibition.…”
Section: Instructed Retrieval Inhibitionsupporting
confidence: 75%
“…Consequently, if RIF is due to interference, it should be observed following either study or retrieval practice, whereas if RIF depends on inhibition, it should be retrieval dependent. Anderson et al (2000;see also Bäuml, 2002;Bäuml & Aslan, 2004;Ciranni & Shimamura, 1999;Shivde & Anderson, 2001) demonstrated, using an episodic memory task, that RIF occurred with retrieval practice, but not with study practice.…”
Section: Stimuli and Designmentioning
confidence: 99%